The Legal Paradigm of Land Acquisition for The Development of The Capital of The Nusantara - Wulandari, Miftah Hayatun Suci; Suriani, Rollys (Mahadi: Indonesia Journal of Law, 2022)
Abstract Law Number 3 of 2022 concerning the State Capital was established to realize the goals of the state as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia. This study aims to determine the procedure for acquiring land in the IKN area and to analyze whether the regulations governing land acquisition in the IKN area have accommodated protection of local people’s human rights. This research is a type of normative legal research, namely legal research conducted by researching and reviewing laws and regulations, using a statute approach and a conceptual approach. Data collection techniques are carried out by collecting primary legal data and secondary legal data. The results showed that the land acquisition procedure in the IKN area consisted of 2 (two) mechanisms, namely by releasing forest areas and through land acquisition mechanisms. The regulations governing the acquisition of land have not fully accommodated the human rights protection of the local community.